Perancangan Arsitektur dalam Mewujudkan TPS 3R Banjar Adat Mambal Kajanan, Desa Mambal, Kabupaten Badung, Bali - I Wayan Widanan; Made Suryanatha Prabawa (Fakultas Teknik Universitas Warmadewa, 2022)
This Community Service Activity aims to provide science and technology services for the community, especially architectural design science and technology. Partners namely Banjar Adat Mambal Kajanan represented by Kelian Adat Mr. Ir. I Wayan Suamba needs the help of a team of architectural design experts to create an Integrated Waste Management Center that can be used to solve the waste problem at the Mambal Market. The service process begins with an initial Focus Group Discussion (FGD) which discusses the need for space and land location, then proceeds with a survey of land conditions, drawing the Waste Management Center building, and ends with an Architectural Design FGD with the Banjar Adat Mambal Kajanan and the Environment and Hygiene Service. (DLHK) Badung Regency.